Local harvest of pig-nosed turtle (Carettochelys insculpta) in the Kao River, Boven Digoel District, Southern Papua, Indonesia - MIRZA D. KUSRINI; RICHARD GATOT N. TRIANTORO; RAMDANI MANURUNG; REZKY AGUST SETIAWAN; NAMHONG KIM (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Kusrini MD, Triantoro RGN, Manurung R, Setiawan RA, Kim N. 2024. Local harvest of pig-nosed turtle (Carettochelys insculpta) in the Kao River, Boven Digoel District, Southern Papua, Indonesia. Biodiversitas 25: 522-532. The pig-nosed turtle has been harvested in the Papuan region, including Merauke area in South Papua province, Indonesia. This study aimed to observe the harvesting characteristics of pig-nosed turtles around the Kao River in Boven Digoel district, South Papua. We interviewed harvesters, collectors, and village officials and participated in harvesting during harvest season, coinciding with the nesting season in August to early November 2022. The use of the pig-nosed turtle on the Kao River is primarily for eggs, not for meat. The collected eggs were incubated in an ex-situ hatchery until the juvenile form was sold to the collectors. All egg harvesters are local Papuans, while collectors or buyers are generally of non-Papuan descent. Harvesting is carried out by local people in land-owned nesting habitats as part of their inheritance-based customary rights. At least 23 clans from two tribes in the Kao River have the customary rights to harvest pig-nosed turtle eggs. Since harvesting has been carried out for more than 10 years, there is a need to ensure that harvesting will be sustainable without sacrificing the local communities' economic benefit.